2023
DOI: 10.9734/ajacr/2023/v13i1233
|View full text |Cite
|
Sign up to set email alerts
|

Application of Response Surface Methodology (RSM) for Optimizing Turbidity of Paper Recycling Wastewater Using Microwave Technology

Abstract: Aims: The aim of the study was to use Response Surface Methodology (RSM) to find optimal experimental design for wastewater treatments from office paper recycling.  In this way, interactive effects of treatment factors were evaluated, including microwave power (MW) and durations with centrifuge time while turbidity of wastewater was chosen as the dependent output variable or an optimal response. Methodology: The RSM approach was utilized for optimization of the process parameters and identifying the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Besides visual analysis, it was suggested to measure the cloudiness-haziness (Turbidity) of wastewater using a turbidity method (Stephenson and Duff, 1996;Choy et al, 2016;Özkan and Sahin, 2023;Ozkan et al, 2023). The turbidity values of wastewater samples are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides visual analysis, it was suggested to measure the cloudiness-haziness (Turbidity) of wastewater using a turbidity method (Stephenson and Duff, 1996;Choy et al, 2016;Özkan and Sahin, 2023;Ozkan et al, 2023). The turbidity values of wastewater samples are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…It mainly involves processes, including furnish preparation, pulp treatment, and paper web formation. Although the quantity of water consumption varies for each mill depending on the desired paper grade, it requires fresh water for every tonne of paper manufactured (Biermann, 1996;Ozkan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides synthetic materials, various cost-effective natural adsorbents such as agricultural and forest residues have also been utilized as bio-absorbents for treatment purposes (Janoš et al, 2009;Zedan et al, 2022). It has suggested that the ash raw bagasse (Valix et al, 2004), plant stem (Bazrafshan and Kord Mostafapour, 2013), cellulose-based waste (Annadurai et al, 2002), red pine chips (Ozkan et al, 2023) have some of the natural absorbent that effective for removing various type of coloring matters from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported to be use MW irradiated to modify material's properties including; surface and bulk modification (i.e. permeability, wettability, dyeability and bonding ability), pyrolysis of lignocellulosics, phase separation and extraction, remediation of hazardous and radioactive wastes and sewage sludge treatments (Ozcelik and Sahin, 2021;Ozkan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%